Corpo, violência e estado: percepções de operadores do sistema de justiça criminal acerca do homicídio de pessoas LGBTQI+ - Melo, Mariana Soares Pires (2020)
This work analyses the perceptions of criminal justice system workers about murders with LGBT victims in Paraíba state, Brazil. I have conducted participant observations at police stations, state departments, jury courts, and interviews with 16 juridical operators from the criminal justice system (judges, district attorneys, public defenders, and police officers) and 2 bureaucrats from the state administration. It was possible to note that the definition of categories, documents, arguments, and strategies undertaken by these state actors, build the definition of homophobic motivation and its characteristics at Intentional Lethal Violent Crimes (Crimes Violentos Letais Intencionais) cases (CVLI). Thus, we put a look at the process of framing (BUTLER, 2015) used by legal state actors to comprehend murders cases against LGBTQI+ community. This makes it possible for us to understand how those workers build meaning around categories such as hate, homophobia, and vulnerability. This scenario also allows us “to see” how the State legitimates itself towards the society, by the controlling of queer bodies. We reflect, therefore, about the connections among State, body, and violence.